Another look at housing finance in Africa: The anatomy of pension asset-backed housing financing. Issue 1 (7th March 2016) - Donkor-Hyiaman, Kenneth Appiah; Owusu-Manu, DeGraft
Abstract : Purpose: – Most households in Sub-Saharan African cannot afford adequate housing. Most often, their pension benefits are also meagre, usually resulting from low contribution levels and mismanagement. Coupled with low life expectancies, most would not live to enjoy the benefits of pensions, thus validating the need to utilize their hitherto deferred pension benefits for immediate housing investment and consumption. Design/methodology/approach: – Quantitative research methodology via the present value technique was used in valuing pension benefits to demonstrate the potential of pension schemes as savings mobilization mechanisms for long-term pension-backed housing financing in Ghana. Findings: – Policy wise, the paper provides some evidence to support proposals for the development of pension-backed housing finance systems in Ghana with lessons for Sub-Saharan Africa. The authors demonstrate that the Tier 2 defined contribution mandatory occupational pension scheme could serve the purpose of a savings mobilization mechanism for long-term housing financing. The authors observe that by increasing the Tier 2 contribution rate to 30 per cent, the majority of the sample, mainly of the middle-income class, could accumulate between US$11, 000 and US$17, 000 over their working life. At the same rate, between US$5, 783 and US$9, 550 could have been raised as savings between 2010 (when implementation began) and 2014. This could form a substantial equity contribution in a mortgage investment and or borrowed on a housing microfinance basis. Originality/value: – The paper contributes to the ongoing debate on the need to develop alternate savings mechanisms and collateral assets using pension assets, other than property, for mortgage financing. The proposals made are aimed at influencing policy by way of advocating for the use of latent pension equity to improve the housing conditions of members while they are alive, and also to suggest pension-backed housing financing as an alternative investment option. A comprehensive study would be required to settle issues of scalability, pricing and model design.